From trauma to trust: the initial psychometric evaluation of a survey instrument measuring trauma among transgender women in the US deep south - Van Gerwen, Olivia T.; Day, Katelyn S.; Aaron, Kristal J.; Lindl, Hannah M.; Miller, Gabe H.; Batey, D. Scott; Siwakoti, Krishmita; Wall, Jay; Patterson, Brianna; Turan, Bulent; Muzny, Christina A. (Frontiers in Public Health, 2025)
BackgroundTransgender women (TGW) experience unique life traumas that may perpetuate negative sexual health outcomes, such as high rates of HIV and sexually transmitted infections. This is especially true in the US Deep South, where structural and cultural factors further marginalize gender minorities as well as people of color. Providing trauma informed care to TGW in sexual and reproductive health (SRH) settings is necessary, but strategies to measure traumatic experiences among this population are needed. We aimed to develop and psychometrically assess a multi-item survey instrument evaluating trauma-specific histories for use with TGW in SRH settings and assess differences in reported trauma histories between White and non-White TGW in the US Deep South.MethodsSurvey items were developed using three existing general trauma instruments (Life Events Checklist for DSM-5, Trauma History Questionnaire, Stressful Life Events Screening Questionnaire) and results from qualitative interviews with TGW. Survey items fell into five trauma subdomains: healthcare-related experiences, sexual/relationship experiences, crime-related/general trauma experiences, gender dysphoria experiences, and discrimination experiences. A computer-assisted self-interviewing instrument was administered to TGW. Descriptive statistics were calculated. Cronbach’s alpha coefficients (α) were calculated for each subdomain to determine internal consistency. Results were stratified by race (White versus non-White), and means of trauma subdomain results were compared.ResultsBetween April 2024–September 2024, 105 TGW enrolled and completed the instrument. Median participant age was 30 years (range 19–73), and most identified as White (n = 55) or Black/African American (n = 40). Mental health conditions such as depression (n = 64) and anxiety (n = 59) were common. Psychometric analyses revealed acceptable internal constancy for the subdomains of healthcare-related experiences (α = 0.787), crime-related/general trauma experiences (α = 0.870), and discrimination experiences (α = 0.870). Subdomains measuring sexual/relationship experiences and gender dysphoria had lower reliability (α = 0.597 and 0.499, respectively). Trauma in all subdomains was common among all participants, with traumatic sexual and relationship experiences (p = 0.004) and crime-related and general trauma experiences (p < 0.001) reported more frequently among non-White participants and gender dysphoria experiences (p < 0.001) reported more frequently among White participants.ConclusionTGW experience trauma in multiple domains, and the intersection of race and gender minority status appears to influence these findings. This instrument has the potential to facilitate trauma assessment in SRH clinical settings and embolden providers to provide care through a trauma informed lens.